A review of photovoltaic performance of organic/inorganic solar cells for future renewable and sustainable energy technologies. (July 2020) - Ajayan, J.; Nirmal, D.; Mohankumar, P.; Saravanan, M.; Jagadesh, M.; Arivazhagan, L.
Abstract: Solar cells are emerging as serious contenders to rival leading energy sources to generate electricity for environment friendly renewable and sustainable energy technologies. Earth is receiving an incredible amount of solar energy which can be converted into electricity by means of high-performance solar cells for meeting the future global energy needs. This article reviews the rapid progress in the developments of inorganic and organic solar cells (SCs) such as silicon SCs, perovskite SCs, III-V SCs, quantum dot SCs, dye sensitized SCs, flexible SCs, thin film SCs and tandem SCs. This article highlights the factors influencing the photovoltaic (PV) performance of SCs such as solar cell architectures, photovoltaic materials, photo-electrode materials, operational and thermal stability challenges, recombination losses, thermal and chemical treatments, trap defects, hole transport materials and optical irradiation. This paper also point out the reliability issues and challenges in the commercialization of SCs. Solar cells are emerging as a promising solution for power generating windows, power saving display systems, self-powered flexible and wearable electronic devices, building integrated photovoltaics, charging of e-vehicles, space craft and satellite applications and solar lighting. Highlights: The role of solar cells for future renewable and sustainable energy applications. Highlights the factors influencing the photovoltaic (PV) performance of solar cells. Reliability issues and challenges in the commercialization of solar cells. Recent developments in organic and flexible solar cells.